Manifestations of narrative language in the novel "The Thief and the Dogs" Naguib Mahfouz - Kayal, Hadeel (Journal of Arabic Language Sciences and Literature, 2024)
The research explores the role of narrative language in "The Thief and the Dogs" novel and delves into its boundaries, examining its various forms and expressions among characters and events. It consists of an introduction and six sections, which shed light on the significance of language within the novel’s context and its alignment with social, cultural, and religious actions. Employing descriptive, deductive, and inductive methods, the study aims to answer key questions such as whether language is merely a neutral tool or the foundation for constructing intricate narratives, and what forms of qualitative performance it assumes within the novel. The research analyzes narrative weaving, dialogic language, and monologue, observing how language manifests in various contexts like memories, dreams, trials, and stream of consciousness. It argues that the novel is essentially a reflection of life, depicting societal realities through prose language that reflects human conflicts. The interaction between narrative and linguistic structures within the novel highlights language as an integral part of characters’ psychological makeup rather than a mere aesthetic feature or container of their thoughts.